2018
DOI: 10.1186/s40352-018-0059-4
|View full text |Cite
|
Sign up to set email alerts
|

The associations of poor psychiatric well-being among incarcerated men with injecting drug use histories in Victoria, Australia

Abstract: BackgroundDual substance dependence and psychiatric and psychological morbidities are overrepresented in prison populations and associated with reoffending. In the context of an increasing prison population in Australia, investigating the needs of vulnerable people in prison with a dual diagnosis can help inform in-prison screening and treatment and improve prison and community service integration and continuation of care. In this study we quantified psychiatric well-being in a sample of people in prison with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 62 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…In addition to standardising data collection across services, this study found no measure of the role of culture in treatment, despite cultural connection and safety being identified as central to each service’s model of care [ 13 , 15 ], Internationally, studies of Indigenous residential rehabilitation services in the US, for example, identified cultural practices (e.g. sweat lodges) in recovery that are important to indigenous peoples [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to standardising data collection across services, this study found no measure of the role of culture in treatment, despite cultural connection and safety being identified as central to each service’s model of care [ 13 , 15 ], Internationally, studies of Indigenous residential rehabilitation services in the US, for example, identified cultural practices (e.g. sweat lodges) in recovery that are important to indigenous peoples [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This group has developed, in partnership with researchers, an evidence-based model of care by using three steps [ 13 ]. First, in-depth qualitative research was undertaken with clients, clinical staff and board members of one residential rehabilitation service to identify the core components of residential rehabilitation treatment perceived to be critical for an effective service [ 15 ]. Second, a systematic review of the existing research literature was undertaken to identify any components of Aboriginal residential rehabilitation services that have been shown to be associated with positive treatment outcomes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among U.S. inmates with mental illness, up to 70% to 75% reported having substance abuse/dependence problems (James & Glaze, 2006; Mumola & Karberg, 2006; Peters et al, 2015). Moreover, incarcerated offenders who had previously used drugs generally reported a history of mental disorders (Cossar et al, 2018; Mumola & Karberg, 2006; Peters et al, 2015). In their study validating two short forms of instruments against three standardized instruments for screening mental disorders, Sacks et al (2007) identified a high rate of mental illness disorders (78.3%) among inmates who were newly admitted to substance abuse/dependence programs across the United States, with half of them reporting having suffered from severe depression and anxiety at some point in their lives.…”
Section: The Prevalence Of Mental Illness and Substance Abuse/dependementioning
confidence: 99%
“…Furthermore, prior research has relied on different definitions to identify individuals who have frequent contact with the justice system, taking into account only arrests for a protective hold (Akins et al, 2016 ), or only jail or incarcerated individuals (Baillargeon et al, 2009 ; Hwang et al, n.d. ; Kopak, Guston, Maness, & Hoffmann, 2019 ; White et al, 2006 ), or only anecdotal evidence from police departments or news media (Santos & Goode, 2014 ). Given the limited samples used in prior studies, the true prevalence of mental illness and SUD among repeat arrestees is unknown (Bailey et al, 2018 ). This is problematic as repeat arrestees are typically presumed to be living with a mental illness (Akins et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%